Psychosocial Factors Associated With Alcohol Use among Persons Aged 18-35 Years in Kangundo North Ward, Machakos County, Kenya - Makau , Joseph; Magu, Dennis; Mambo, Susan; Kirimi, Mwiti (Journal of Health, Medicine and Nursing, 2023)
Purpose: The objective of this study was to explore the psychosocial factors associated with alcohol use among persons aged 18-35 years in Kangundo North Ward, Machakos County. Methodology: A cross sectional study design where data was collected using a structured questionnaire. Data entry was done and analyzed using SPSS version 23, descriptive statistics was used. Logistic regressions were used to explore the psychosocial factors associated with alcohol use where Odds ratios were used. Multivariate and bivariate analysis were done to establish association between psychosocial factors and alcohol use. Findings: 310 respondents were interviewed, the response rate was 100%, 86% were males while 14% were females, 86% of alcohol consumers were males, while 14% who consumed alcohol were females. 89% were aged between 18-24 years, 8% were aged between 25-29 years while 3% were 30-35 years. The study revealed that youths aged 18-35 years suffer a wide variety of challenges.49% of the respondents had experienced financial difficulties, 11% were victims of robbery, these stressful life events can lead to one using alcohol. Majority of respondents had ever experienced stressful event with 50% using alcohol as a solution to relieve the stress. 50.32% indicated that they started taking alcohol after the stressful experiences, 48% had experienced physical violence,5% sexual violence,45% emotional violence while 24% had undergone harsh childhood experiences. The study findings revealed that (28%) had consumed tobacco, (17%) miraa, (8%) marijuana, (1%) inhalants while (46%) had never consumed any psychoactive substance. There was significant association between experiences of emotional, sexual abuse, harsh childhood experiences and use of other psychoactive substances with alcohol use (p<0.05). Unique Contribution to Theory, Practice and Policy: Targeted interventions aimed at addressing psychosocial factors associated with alcohol use is vital. The study adds to the pool of knowledge that psychosocial issues such as stressful life events, gender based violence, harsh childhood experiences and use of other psychoactive substances contribute to alcohol use. Awareness on Gender based violence and other psychoactive substances such as cigarette and marijuana use needs to be enhanced. The findings of the study may inform the local county government of Machakos and Kangundo Sub-county administrators in formulating policies to help address alcohol use among persons aged 18-35 years.